ISOLATION, PURIFICATION AND QUANTITATIVE ANALYSIS OF CYSTEINE PROTEASE, BROMELAIN FROM ANANAS COMOSUS (PINEAPPLE) - HEMANT KR. SHARMA; RICHA SRIVASTAVA; SHUBHANGI SHUKLA (International Journal of Pharma and Bio Sciences, 2014)
Proteases were extracted and assayed from the fruit of Ananas comosus (Pineapple). They were precipitated utilizing variable concentrations of acetone (40%,60%,80%,100%), ammonium sulphate (45%,65%) and Jello (40%,60%,80%,100%). The extracted enzymes exhibited proteolytic activity which was determined using other assay techniques. Activity determined for Ananas comosus was 2U/mL. The enzymes were, in their crude state, analyzed using SDS-AGE. Bands were observed between the molecular weight range of 24-45 KDa. The enzymes were purified from the extract by anion exchange chromatography using Silica Gel Column (pH-8.0, Sodium Phosphate Buffer). The elution of Ananas comosus extract resulted in two bound fractions. Since the second fraction of the Ananas comosus extract exhibited no protease activity, it was ignored. The purified samples were analyzed using SDS-AGE, the purified extract of Ananas comosus displays a single band (characteristic of bromelain, a monomeric molecule).